Polish Media Coverage During the First Stage of the COViD-19 Pandemic. A Qualitative Analysis of Selected Online News Outlets and TV Channels - Łokić, Paweł; Świstoń, Maciej (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2021)
The publication is the result of the the project “Media messages during COViD-19 pandemic”, conducted at the Faculty of Political Science and Journalism at Adam Mickiewicz University in Poznań, Poland. Aim of the publication is to determine the nature (character) of the media broadcasts and publications relating to the first stage of Covid-19 pandemic, as produced by Polish media institutions. Book contains four distinct chapters. The first one presets the assumptions and research aims adopted, as well as the methodology and the discussion of the research sample selection process. The second chapter presents the results of content analysis of online news outlets (onet.pl and wp.pl) studied. This is followed by a chapter presenting content analysis results of news items broadcasted on TVP1, TVN, and Polsat. In the fourth chapter, results presentation has been supplemented by particularly interesting insights from comparative analysis of the online media content vs. TV broadcasts. This comparative analysis serves to underline the observed similarities and differences in reporting across different types of media outlets. Moreover, this publication is to serve as a chronicle of Polish media institutions’ response and the narrative on the first weeks of the Covid-19 pandemic in Poland.
Badania oraz publikację książki sfinansował Uniwersytet im. Adama Mickiewicza w Poznaniu w ramach projektu „Badania nad COVID-19”.
Keywords: COViD-19; pandemia; analiza zawartości mediów; przekazy medialne w pandemii; polskie media o pandemii